2009
DOI: 10.1097/dad.0b013e3181a8527f
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid (CD68+CD123+) Monocytes May Play a Crucial Role in the Pathogenesis of Hydroa Vacciniforme: A Case Report

Abstract: Hydroa vacciniforme (HV) is a rare, blistering, childhood photodermatosis that heals with smallpox-like scars, is associated with latent Epstein-Barr virus (EBV) infection, and spontaneously resolves by early adulthood. Cytotoxic T cells are suspected to mediate the histologic hallmark of HV-dense, perivascular, lymphocytic infiltrates and reticular degeneration and necrosis of the epidermis. We report a case of 13-year-old white girl with EBV-associated HV, whose lesional skin harbored a predominate CD68, CD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Iwatsuki et al 23,26 and others 42,60 showed that both typical and atypical lesions of HV were characterized by the infiltration of EBER-positive T cells, suggesting that they might represent different disease stages across the same spectrum of EBV-associated cutaneous disorders. 26,59 The immunophenotype of HVLL establishes a close relationship with nasal-type extranodal NK/T-cell lymphoma, but this disease usually affects older patients (median age, 50 y) with involvement of the nose, nasal sinuses or the mouth, and the clinical course is highly aggressive with a median overall survival of 8 months, especially for those cases with extranasal involvement and advanced stage disease at diagnosis. 3,45 Primary cutaneous gd-T-cell lymphoma accounts for less than 1% of all cutaneous T-cell lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…Iwatsuki et al 23,26 and others 42,60 showed that both typical and atypical lesions of HV were characterized by the infiltration of EBER-positive T cells, suggesting that they might represent different disease stages across the same spectrum of EBV-associated cutaneous disorders. 26,59 The immunophenotype of HVLL establishes a close relationship with nasal-type extranodal NK/T-cell lymphoma, but this disease usually affects older patients (median age, 50 y) with involvement of the nose, nasal sinuses or the mouth, and the clinical course is highly aggressive with a median overall survival of 8 months, especially for those cases with extranasal involvement and advanced stage disease at diagnosis. 3,45 Primary cutaneous gd-T-cell lymphoma accounts for less than 1% of all cutaneous T-cell lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…pDCs may express CD4 [24] and be mistaken for T-helper cells, may express CXCR3 [33] and be mistaken for lymphocytes, or may express CD68 [34] and be mistaken for macrophages. Conversely, pDCs and endothelial cells express CD123, so care is required in interpreting CD123 immunoreactive material as pDCs [24].…”
Section: Plasmacytoid Dendritic Cells: Producers Of Type 1 Interferonmentioning
confidence: 99%
“…It has been demonstrated that PDCs could appear or be increased in number, in tissues affected by variable pathological conditions: granulomatous lymphadenitis [9], Kikuchi lymphadenitis [10], Castleman's [11], Hodgkin's [12] disease or in allergic rhinitis [13]. More recently, PDCs have been found in skin of patient with psoriasis, lupus erythematosus [14], or hydroa vacciniforme [15].…”
Section: Introductionmentioning
confidence: 96%